The Relationship Between Growth Mindset and Self-Efficacy of Nurses at Hospital 'X' in Bandung during The COVID-19 Pandemic - Trisa Genia C. Zega; Yuni Megarini C.; Meilani Rohinsa; Christopher Mario (Eduvest - Journal of Universal Studies, 2025)
The COVID-19 pandemic has placed extraordinary demands on nurses, increasing their workload and emotional pressure, particularly at Hospital "X" in Bandung. Nurses faced overwhelming challenges requiring clinical skills and strong psychological resilience, including self-efficacy and a growth mindset. However, research exploring the relationship between these two psychological constructs among healthcare professionals remains limited. This study aims to examine the relationship between growth mindset and self-efficacy among nurses during the COVID-19 pandemic. A non-experimental quantitative approach was employed using a correlational method, with data collected via online questionnaires distributed to 233 nurses. Measurement tools included the Generalized Self-Efficacy Scale (GSES) and a Mindset Assessment adapted from Dweck's instrument. The data were analyzed using Pearson correlation through SPSS. The results revealed a significant but weak positive correlation (r = 0.284; p < 0.01) between growth mindset and self-efficacy among nurses. These findings suggest that although belief in the ability to grow (growth mindset) supports confidence in task performance (self-efficacy), the relationship is not strong, indicating that other factors may also influence self-efficacy. The study implies that interventions to strengthen both mindset and self-efficacy could enhance nurses' resilience and performance, particularly during health crises or highly stressful working conditions.